2018
DOI: 10.3855/jidc.9572
|View full text |Cite
|
Sign up to set email alerts
|

Low serum vitamin A is prevalent in underfive children with severe malaria and is associated with increased risk of death

Abstract: Introduction: Micronutrient deficiencies are prevalent in developing countries and may influence vulnerability to diseases particularly malaria and its severity. This study investigated serum vitamin A profile of under-five children with severe malaria (SM) in South-western, Nigeria and to determine its association with degree of malaria parasitaemia, types of SM and eventual outcome. Methodology: Using HPLC, serum vitamin A concentrations of 170 under-five children with SM and 170 age- and gender-matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The relationship between oxidative stress and antioxidant levels is an essential host-related factor as depletion of antioxidants, such as reduced glutathione (GSH), antioxidant vitamins (A, C, and E), and superoxide dismutase (SOD), leads to increased severity of malaria 10 14 . Glutathione peroxidase (GPx) is a member of the oxidoreductase family that catalyzes the conversion of hydrogen peroxide and organic hydroperoxides into water or related alcohols 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between oxidative stress and antioxidant levels is an essential host-related factor as depletion of antioxidants, such as reduced glutathione (GSH), antioxidant vitamins (A, C, and E), and superoxide dismutase (SOD), leads to increased severity of malaria 10 14 . Glutathione peroxidase (GPx) is a member of the oxidoreductase family that catalyzes the conversion of hydrogen peroxide and organic hydroperoxides into water or related alcohols 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Alongside these we noted 12 recent cohort or case–control studies, 15 earlier studies, nine recent cross-sectional studies, 25 older studies, and nine non-systematic reviews. For studies assessing the relationship between vitamin A status and health, growth or development outcomes we identified no systematic reviews, two recent RCTs (with additional data extraction), 39 older RCTs, 17 recent observational studies of which eight appeared particularly relevant [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], 42 earlier cohort or case–control studies, 19 recent cross-sectional studies, 56 earlier cross-sectional studies and eight potentially relevant non-systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
“…As expected from the nature of the question, most of the studies available to address the relationship between vitamin A status and health outcomes were observational, assessing relationships between markers of vitamin A status and autism spectrum disorders [ 39 ], acute or recurrent respiratory infection [ 40 , 43 , 44 , 46 ], asthma [ 42 ], malaria [ 41 ], infectious diseases generally [ 45 ] and mortality [ 41 ] (Excel sheet 2C Status Outcome) .…”
Section: Resultsmentioning
confidence: 99%
“…A study of preschool children showed that the levels of antioxidants A, C, and E in children infected by Plasmodium were low, and that the more severe the infection, the lower the levels of these antioxidants [ 150 ]. Recent studies show that vitamin deficiency can significantly contribute to the increase in disease morbidity and mortality [ 151 , 152 ].…”
Section: Oxidative Stress In the Host Induced By Plasmodiummentioning
confidence: 99%